What counts as mutilation—and who should decide? Disrupting dominant discourses on genital cutting and modification - Earp, BD; Abdulcadir, J; Shahvisi, A (Taylor and Francis, 2024)
This Special Collection of articles in Culture, Health & Sexuality examines diverse genital cutting practices affecting individuals of all sexes and genders across cultures. It challenges dominant narratives and stereotypes, particularly in relation to male circumcision and what the World Health Organisation (WHO) defines as “female genital mutilation” (FGM), while also touching on intersex genital “normalisation” procedures to highlight the complexity and interconnectedness of these practices. The papers reveal that culturally prescribed genital cutting varies widely in methods, meanings, motivations, and outcomes, with simplistic distinctions based on sex, gender, or cultural origin being highly misleading. The collection emphasizes the need for a more holistic, cross-cultural approach to studying and understanding these practices.